AN INTEGRATED MODEL FOR OPTIMIZING RURAL ROAD NETWORK AND PUBLIC FACILITY LOCATION IN DEVELOPING COUNTRIES - NAKANISHI, Hitomi; HIROBATA, Yasuhiro; HENG, Salpiseth (INFRASTRUCTURE PLANNING REVIEW, 2007)
In many developing countries, the poor geographical accessibility has made rural residents isolated from opportunities which improve quality of life. The objective of this study is to provide an integrated model for optimal road network and multi-type public facility location design considering budget constraint. The model is simulated with the real road network in puok district, Cambodia. It is found that investment in many small size facilities distributed among villages along with a provision of a good basic earth road seems to be the most cost-effective approach in the study area.